2017
DOI: 10.20996/1819-6446-2017-13-3-403-408
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Significance of Cardiac Arrhythmias

Abstract: Аритмии являются одной из актуальных проблем современной кардиологии. Широкий спектр клинических проявлений нарушений ритма сердца (НРС), выявление их как при различных заболеваниях, так и у здоровых людей обуславливают потребность изучения их распространенности в популяциях. В большинстве проведенных эпидемиологических исследований использовалась однократная регистрация электрокардиограммы (ЭКГ), наиболее доступный для обследования больших групп населения, но малоинформативный метод выявления аритмий. Небольш… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Порушення ритму серця -одна з найбільш актуальних і складних проблем сучасної кардіології. Аритмії часто зустрічаються як у хворих із серцево-судинними захворюваннями, так і серед здорових осіб, нерідко спричиняючи смерть та інвалідизацію [1][2][3][4]. Останніми роками для лікування суправентрикулярних аритмій, особливо фібриляції передсердь (ФП), значного поширення набула транскатетерна абляція, однак важливу роль у лікуванні пацієнтів, як і раніше, відіграють антиаритмічні препарати (ААП) [1,5,6].…”
Section: ключові слова: аритмія; лікування; флекаїніду ацетат; фібриляція передсердь; флекаїнідunclassified
“…Порушення ритму серця -одна з найбільш актуальних і складних проблем сучасної кардіології. Аритмії часто зустрічаються як у хворих із серцево-судинними захворюваннями, так і серед здорових осіб, нерідко спричиняючи смерть та інвалідизацію [1][2][3][4]. Останніми роками для лікування суправентрикулярних аритмій, особливо фібриляції передсердь (ФП), значного поширення набула транскатетерна абляція, однак важливу роль у лікуванні пацієнтів, як і раніше, відіграють антиаритмічні препарати (ААП) [1,5,6].…”
Section: ключові слова: аритмія; лікування; флекаїніду ацетат; фібриляція передсердь; флекаїнідunclassified
“…Cardiac Arrhythmias are one of the most complexes, insufficiently studied, and therefore one of the most urgent problems of modern cardiology (Zatonskaya et al, 2017), Cardiovascular diseases (CVDs) are the leading cause of death globally. An estimated 17.9 million people died from CVDs in 2019, representing 32% of all global deaths.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…4 Cardiac arrhythmias are one of the most complex, insufficiently studied, and therefore one of the most urgent problems of modern cardiology. 5 Knowledge is essential for prevention of errors and providing higher quality care. 6 Studies in India and other developed countries revealed that nurses are having less knowledge regarding identification and management of cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 99%